“It gets your foot in the door”: An examination of the Healthy Apples Self-Care Program at Durham Regional Police Service - Rosemary Ricciardelli; Mark Jones; Evan Cross; Krystle Martin; Stanley R. MacLellan (Social Sciences and Humanities Open)
The psychological strain inherent to the policing profession and the effect of psychological strain on sworn and civilian members are increasingly recognized. The effects of stress can be wide-ranging, including an increased risk for occupational or posttraumatic stress injuries. Police services have implemented a variety of wellness programs; however, little is known about the benefits and challenges of these programs. In the current study, we examine one such program, the Healthy Apples Self-Care Program, which entails mental and physical health ‘check-ins’. Semi-structured interviews with 76 police members, sworn and civilian, from January 2024 through April 2024 were completed. In total, 44 men and 32 women were interviewed for this study – 75 % of whom reported using the Healthy Apples Program. Interviews analyzed using a semi-grounded thematic approach. Responses indicated overwhelming support for the program with several benefits identified such as learning about themselves and new psychological skills, facilitating more engagement with mental health resources, and building a culture of wellness. Challenges were also noted such as the lack of time or difficulty with scheduling program activities, lack of access to care providers (i.e., medical doctors), administrative burden of participating, and lack of knowledge about the process. Results provide rich descriptions of aspects of the wellness program and offering strong support for police organizations to provides the program yet highlight pitfalls for organizations to avoid or address.